2018
DOI: 10.1152/ajpheart.00071.2017
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of physiological late Na+ current stabilizes ventricular repolarization

Abstract: The physiological role of cardiac late Na current ( I) has not been well described. In this study, we tested the hypothesis that selective inhibition of physiological late I abbreviates the normal action potential (AP) duration (APD) and counteracts the prolongation of APD and arrhythmic activities caused by inhibition of the delayed rectifier K current ( I). The effects of GS-458967 (GS967) on the physiological late I and APs in rabbit isolated ventricular myocytes and on the monophasic APs and arrhythmias in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
7
7
0
Order By: Relevance
“…However, TTX-sensitive Na+ channels (Na v 1.1–1.4, Na v 1.6– 1.7) are less likely to contribute to I NaL here. This agrees with the reported IC 50 values of 1–2 ^M for TTX I NaL inhibition in rabbit [51], guinea-pig [33, 52] and human [1] ventricular myocytes, although TTX- sensitive Na+ channel isoforms have been reported to contribute to I NaL in heart failure [53]. Moreover, TTX-resistant Na v 1.8 channels have also been suggested to be expressed and contribute to I NaL in mouse, rabbit [54] and failing human [55] ventricular myocytes.…”
Section: Discussionsupporting
confidence: 93%
“…However, TTX-sensitive Na+ channels (Na v 1.1–1.4, Na v 1.6– 1.7) are less likely to contribute to I NaL here. This agrees with the reported IC 50 values of 1–2 ^M for TTX I NaL inhibition in rabbit [51], guinea-pig [33, 52] and human [1] ventricular myocytes, although TTX- sensitive Na+ channel isoforms have been reported to contribute to I NaL in heart failure [53]. Moreover, TTX-resistant Na v 1.8 channels have also been suggested to be expressed and contribute to I NaL in mouse, rabbit [54] and failing human [55] ventricular myocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly to our results, V + max was reduced by 0.3 µM GS967 in murine myocytes [49] , while the same concentration of the drug failed to modify V + max in canine Purkinje strands [50] . On the other hand, GS967 shortened APD in a variety of preparations, including rat [51,52] , murine [49] , rabbit [16,53] and human [54] ventricular cells within a wide concentration range (0.1-1 µM)similarly to the present observations in isolated canine ventricular cells. In our multicellular preparations, however, a signi cant APD shortening effect appeared only at cycle lengths longer than 1.5 s. This can be explained by the well-known higher drug-sensitivity of single cells comparing to multicellular preparations.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together the present results and the literature, it is likely that a compound having kinetic properties similar to GS967 would be a very promising new antiarrhythmic agent, since several in vitro [16][17][18][19][49][50][51][52][53][54] and in vivo [51,55] studies support the potent antiarrhythmic activity of GS967. Its kinetic properties are better than those of mexiletine, as shown in this study, and also than those of ranolazine [9] , agents known to suppress I NaL .…”
Section: Discussionsupporting
confidence: 76%
“…To investigate a possible role for late INa in cardiac action potential, we measured the effect of the selective late INa inhibitor GS-967 49 , 51 . In current clamp recording of action potentials induced by current injection in isolated adult human ventricular cardiomyocytes, we found that the application of 0.1 µM GS-967 decreased the action potential duration and reduced the temporal variability in action potential duration at 90% repolarization (APD90) between consecutive beats, a biomarker for pro-arrhythmia 52 , quantified as short-term variability in APD90 (STV(APD90)) (Fig.…”
Section: Resultsmentioning
confidence: 99%